Evaluation and discussion of handmade face-masks and commercial diving-equipment as personal protection in pandemic scenarios - Gierthmuehlen, Mortimer; Kuhlenkoetter, Bernd; Parpaley, Yaroslav; Gierthmuehlen, Stephan; Köhler, Dieter; Dellweg, Dominic (PLOS ONE, 2020)
Objective Pandemic scenarios like the current Corona outbreak show the vulnerability of both globalized markets and just-in-time production processes for urgent medical equipment. Even usually cheap personal protection equipment becomes excessively expensive or is not deliverable at all. To avoid dangerous situations especially to medical professionals, but also to affected patients, 3D-printer and maker-communities have teamed up to develop and print shields, masks and adapters to help the medical personnel. In this study, we investigate three home-made respiratory masks for filter and protection efficacy and discuss the results and legal aspects. Materials and methods A home-printed respiratory mask with a commercial filter, a scuba-diving mask with a commercial filter and a mask sewn from a vacuum cleaner bag were investigated with 99mTc-labeled NaCl-aerosol, and the respective filter-efficacy was measured under a scintigraphic camera. Results The sewn mask from a vacuum cleaner bag had a filter efficacy of 69.76%, the 3D-printed mask of 39.27% and the scuba-diving mask of 85.07%. Conclusion Home-printed personal protection equipment can be a–yet less efficient–alternative against aerosol in case professional masks are not available, but legal aspects of their use and distribution have to be kept in mind in order to avoid compensation claims.